2016
DOI: 10.1002/jmrs.156
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three different VMAT techniques for the delivery of lung stereotactic ablative radiation therapy

Abstract: IntroductionThe purpose of this study was to investigate coplanar and non‐coplanar volumetric modulated arc therapy (VMAT) delivery techniques for stereotactic ablative radiation therapy (SABR) to the lung.MethodsFor ten patients who had already completed a course of radiation therapy for early stage lung cancer, three new SABR treatment plans were created using (1) a coplanar full arc (FA) technique, (2) a coplanar partial arc technique (PA) and (3) a non‐coplanar technique utilising three partial arcs (NCA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…Fitzgerald et al compared three types of VMAT plans for lung SABR, which were coplanar full arc (CFA), coplanar partial arc (CPA), and non-coplanar partial arc (NPA) VMAT plans. 4 They demonstrated that the NPA plans improved conformity of the PTVs while reducing irradiation of body by intermediate doses as well as the maximum doses to spinal cord. In that study, the locations of the target volumes were various in both lungs and the number of cases analyzed in that study was limited (10 cases); therefore, a deep analysis on the benefit of the NPA plans could not be performed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Fitzgerald et al compared three types of VMAT plans for lung SABR, which were coplanar full arc (CFA), coplanar partial arc (CPA), and non-coplanar partial arc (NPA) VMAT plans. 4 They demonstrated that the NPA plans improved conformity of the PTVs while reducing irradiation of body by intermediate doses as well as the maximum doses to spinal cord. In that study, the locations of the target volumes were various in both lungs and the number of cases analyzed in that study was limited (10 cases); therefore, a deep analysis on the benefit of the NPA plans could not be performed.…”
mentioning
confidence: 99%
“…1,2 To achieve high local control rate and low toxicity of lung SABR, various treatment planning techniques utilizing non-coplanar beams were proposed and investigated to acquire an optimal dose distributions. [3][4][5][6][7] Dong et al proposed 4π non-coplanar plans to reduce doses to organs at risk (OARs), while improving planning target volume (PTV) coverage for centrally located or large lung tumors. 3 They showed superior plan quality to that of volumetric modulated arc therapy (VMAT) with two full arcs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fitzgerald et al. reported their experience with 3DCRT and VMAT at this journal issue . The CyberKnife (Accuray, Sunnyvale, CA) system has a unique treatment planning system based on robotically directed beam delivery.…”
Section: Treatment Planningmentioning
confidence: 99%
“…recent studies, [4][5][6][7][8] SBRT has exhibited favorable clinical outcomes. To achieve a high local control rate and a low toxicity, SBRT treatment of the lung cancer has been performed on gantry-mounted linear accelerators (LINACs) using noncoplanar or coplanar three-dimensional conformal radiation therapy (3DCRT), 9,10 intensity modulated radiation therapy (IMRT), 10,11 and volumetric modulated arc therapy (VMAT) [12][13][14] to acquire optimal dose distributions [15][16][17][18] and increase the efficiency of treatment delivery.…”
mentioning
confidence: 99%